Coverage of the opioid crisis in national network television news from 2000–2020: A content analysis. Issue 1 (1st December 2022) - Jay, Jessica; Chan, Amy; Gayed, George; Patterson, Julie
Abstract: Background: News coverage has both negatively and positively influenced public awareness and perceptions surrounding the opioid crisis. This study aimed to describe and analyze national network television news framing of the scope and impact of the opioid crisis in the United States. Methods: We performed a retrospective content analysis on national network television evening news segments covering the opioid crisis from 1/2000 to 8/2020, which were obtained from the Vanderbilt Television News Archive. The database was queried for: opioid epidemic, oxycontin, heroin, fentanyl, and naloxone. Two independent reviewers quantitatively coded segment characteristics, including theme, geographic location, opioids mentioned, strategies for combatting the epidemic discussed, interviews conducted, and patient demographics. Changes in segment characteristics over time were analyzed using chi-square analyses and Fisher's exact tests. Results: News segments ( N = 191) most commonly provided an overview of the epidemic (55.5%) and/or conveyed personal stories (40.3%). Prescription opioids (59.7%) and heroin (62.8%) were more often referenced than fentanyl (17.8%); the focus on heroin peaked in 2011–2015 (84.8%), while references to fentanyl significantly increased over time ( p = 0.021). The most frequently interviewed people included patients with opioid use disorder (OUD) (47.1%), healthcare providers (36.7%), family members/friends (31.9%), and law enforcement (30.9%). Most of the featured patients with OUD were male (63.0%), white (88.4%), and young (< 40 years) adults (77.9%). Coverage of the crisis peaked in 2016. Conclusions: Evening news segments' emphasis on personal stories, while emotionally compelling, came at the cost of thematically-framed coverage that may improve public understanding of the complexities of the epidemic. The depiction of primarily white, young adult patients with OUD revealed a need for a greater emphasis in the news on underrepresented minorities and older adults, as these populations face additional stigma and disparities in OUD treatment initiation and retention.